Seismic Behavior of Stone Masonry Joints with ECC as a Filling Material - Wei Hou (MDPI AG, 2021)
This paper investigates the seismic behavior of novel stone masonry joints using ductile engineered cementitious composite (ECC) as a substitute for ordinary mortar. Ten stone masonry joints with different types of mortar/ECC were tested under axial and cyclic loads. The filling materials of mortar joints tested included ordinary mortar, polymer mortar, ECC, and composite mortar with two combination proportions of ECC and ordinary mortar. The test results indicated that ECC specimens exhibited a more stable hysteretic response as well as an improvement in strength, deformation, energy dissipation, and strength degradation. The ECC mortar joints maintained integrity during the entire loading process due to the “self-confinement” effect of ECC. A partial substitution of mortar with ECC could provide effective reinforcement and confinement to prevent mortar failure and peeling, thereby allowing such specimens to approach the seismic performance of ECC specimens. Based on the trend of shear strength variations, a corresponding failure process is defined for ECC/mortar joints under cyclic and axial compressive loads, including four distinct stages: linear elastic, crack-developing stage, interface debonding, and friction sliding. New equations are proposed for predicting the shear strength and residual shear strength of the ECC/mortar joints on the basis of the test results, which are validated in the composite mortar specimens.